PPPoE internet access for government-enterprise customer in LSN environment - Yongming YAN; Kechuang YE; Bin XU; Haifeng XU; Liang ZUO; Kaiyuan HONG (Dianxin kexue)
With the blowout development of cloud-computing market,start-up enterprises gradually increase the demand for cloud business.For the cost-sensitive customers,using the traditional government-enterprise PPPoE in the LSN environment could reduce the wastage of public IPv4 addresses.Meanwhile,ICT services based on cloud-computing was provided for customers.Several solutions which mixed the traditional government-enterprise gateway solution and the latest LSN scene were presented.Through the analysis of advantages and disadvantages of each scheme,reference for government-enterprise customers dialing-up to access internet in LSN environment was presented.